Aplicación De Mejora Continua Para Disminuir Los Tiempos Muertos En El Area De Inyeccion De Plasticos - Arroyo Flores, David Gerardo (2017)
The purpose of this study was to establish a methodology for the application of a continuous improvement tool to reduce dead times in the area of plastic injection in the company Geka Corp. S.A.C. The application of the present methodology was carried out in the area of plastic injection. For this purpose, the method of Comparative design was used; Using techniques of Observation of the current process, Interviews and poll with plant engineers; Head of quality control, head of Logistics and questions to workers in the process area. The effect or impact of the Continuous Improvement tool application in the plastic injection company is highly positive because of the decrease in downtime. According to the diagnosis of the plastic injection, process the respective times in each operation is decreased by 65.6% taking into account that cleaning and descaling of the cooling system takes a time of 1,2 hours. The use of an electromechanical winch or winch system was considered mainly in the assembly and dismantling of the molds, reducing the dead time by 79.0%